A Cross-Sectional Overview: The Effect of the Covid-19 Pandemic on the Flow Rate of Orthopedic Trauma Cases in Kuwait - Alsaifi, Saleh; Boskandar, Ahmad; Alkhaldi, Saleh; Khaja, Aliaa; Alhadhoud, Meshal (International Journal of Innovative Research in Medical Science, 2020)
Objective: The COVID-19 pandemic has led many countries to carry out a range of restrictions ranging from social distancing rules to full national lockdowns. The main aim of this study was to compare the flow rates of orthopaedic trauma injuries in Kuwait prior to the partial lockdown and during the curfew period. Method: Patient records for 641 isolated traumatic orthopedic injuries were collected pre and post the nationwide enforced partial curfew. The data was collected from the registries of 3 major orthopedic centers in the country. These hospitals cover a total of about 5 million people. Results: Hospitals of Kuwait received 356 patients in March-April of 2019 and 285 in the same months of 2020 during the curfew period. A slight decrease in the flow of orthopedic injuries was noted in the curfew period, but not a statistically significant one. Male to female ratio remained the same for both groups as well as the ratio for age groups. Femur fractures in the 2020 group were slightly higher and spine fractures were slightly lower than they were in 2019. Conclusion: A slight decrease in the number of patients who had orthopedic traumatic injuries was noted during the COVID-19 enforced partial curfew period. The decreased rate however, was not statistically significant.